A Variant of the Autophagy-Related 5 Gene Is Associated with Child Cerebral Palsy - Xu, Jianhua; Xia, Lei; Shang, Qing; Du, Jing; Zhu, Dengna; Wang, Yangong; Bi, Dan; Song, Juan; Ma, Caiyun; Gao, Chao; Zhang, Xiaoli; Sun, Yanyan; et al. (Frontiers in Cellular Neuroscience, 2017)
Cerebral palsy (CP) is a major cause of childhood disability in developed and developing countries, but the pathogenic mechanisms of CP development remain largely unknown. Autophagy is a highly conserved cellular self-digestion of damaged organelles and dysfunctional macromolecules. Growing evidence suggests that autophagy-related gene 5 (ATG5)-dependent autophagy is involved in neural development, neuronal differentiation, and neurological degenerative diseases. The aim of this study was to analyze ATG5 protein expression and gene polymorphisms in Chinese patients with CP and to evaluate the importance of ATG5 in the development of CP. Five polymorphisms from different regions of the ATG5 gene (rs510432, rs3804338, rs573775, rs2299863, and rs6568431) were analyzed in 715 CP patients and 658 controls using MassARRAY. Of these, 58 patients and 56 controls were selected for measurement of plasma ATG5 level using ELISA. The relevance of disease-associated SNPs was evaluated using the SHEsis program. We identified a significant association between rs6568431 and CP (OR = 1.388, 95% CI = 1.173 1.643, Pallele = 0.0005, Pgenotype = 0.0015). Subgroup analysis showed a highly significant association of rs6568431 with spastic CP (n = 468, OR = 1.511, 95% CI = 1.251 1.824, Pallele = 8.50e-005, Pgenotype = 1.57e-004) and spastic quadriplegia (OR = 1.927, 95% CI = 1.533 2.421, Pallele = 7.35e-008, Pgenotype = 3.24e-009). Furthermore, mean plasma ATG5 levels were lower in CP patients than in controls, and individuals carrying the AA genotype of rs6568431 that was positively associated with CP had lower plasma ATG5 levels (P < 0.05). This study demonstrated an association of an ATG5 gene variant and low level of ATG5 protein with CP, and stronger associations with severe clinical manifestations were identified. Our results provide novel evidence for a role of ATG5 in CP and shed light on the molecular mechanisms underlying this neurodevelopmental disorder.